The Gph–M.I.L.F. Agreement: human rights provisions and possible overlaps - Fajri Matahati Muhammadin (Jurnal Cita Hukum, 2014)
Abstract: The GPH – M.I.L.F. Agreement: Human Rights Provisions and Possible Overlaps. One of the challenges in ending non-international armed conflicts is to conclude a peace agreement that satisfies the need of both parties. A new approach to this is the human rights approach, which seeks to observe and promise to fulfil elements of human rights as terms of peace. The ongoing peace process in the Philippines between the Government and the Moro Islamic Liberation Front is seeing positive progress, with its peace agreement provisions highly based upon human rights. However, there are potential problems in implementing these provisions, as well as overlaps with the pre-existing structure or even between the human rights provisions themselves. This essay will observe the problems and overlaps particularly on provisions related to the rights of religion and women, and how they can be addressed. Abstrak: Perjanjian GPH-MILF: Ketentuan Hak Asasi Manusia dan Kemungkinan Terjadinya Tumpang tindih. Salah satu tantangan dalam mengakhiri konflk non internasional adalah menyusun perjanjian damai yang memuaskan kedua belah pihak. Sebuah pendekatan baru dalam perjanjian damai adalah pendekatan Hak Asasi Manusia (HAM) yang mengamati dan berkomitmen memenuhi elemen-elemen HAM sebagai syarat dalam perjanjian damai. Proses perdamaian antara Pemerintah dan Moro Islamic Liberation Front yang masih berlangsung di Filipina saat ini memiliki kemajuan yang positif. Perjanjian-perjanjian yang sudah ditandatangani tampak jelas dilandasi oleh HAM. Akan tetapi tampak kemungkinan beberapa masalah implementasi serta kontradiksi antara ketentuan HAM dalam perjanjian damai dengan struktur yang telah ada, dan bahkan antar ketentuan HAM dalam perjanjian itu sendiri. Tulisan ini akan mengamati implementasi dan kontradiksi dalam perjanjian damai ini terutama terkait hak beragama dan hak wanita dan bagaimana permasalahan tersebut dapat diselesaikan. DOI: 10.15408/jch.v1i1.1449